The Effect of Strawberries as a Natural Teeth Whitening Agent on Tooth Surface Roughness: In Vitro Study - Tanjung, Dian Soraya; Daryono; Yemima Christy Ginting (Community Medicine and Education Journal, 2024)
Teeth whitening due to discoloration can be achieved by methods of bleaching. The material used in bleaching conventional methods can have effects on hard tooth tissue, such as increasing tooth surface roughness. Strawberries (Fragaria x ananassa) have long been known for being effective in whitening teeth. The aim of the research was to determine the effect of strawberries as a natural teeth whitening agent on tooth surface roughness in vitro. This research is an in vitro experiment. The samples were 24 first premolars of the upper jaw and lower jaw, which were divided into two groups. Group 1 (strawberry juice 100%) and group 2 (carbamide peroxide 10%). Testing tooth surface roughness using tools surface roughness tester, then the data was analyzed using statistical test paired t-test and Mann-Whitney. The results of the study showed that the mean and standard deviation of tooth surface roughness before and after application of strawberry fruit juice was 0.37 ± 0.156 and 0.22 ± 0.129, while the 10% carbamide peroxide group obtained the value of tooth surface roughness before and after application was 0.36 ± 0.118 and 0.37 ± 0.263.